Robust older adults in primary care: factors associated with successful aging - Luciana Colares Maia; Thomaz de Figueiredo Braga Colares; Edgar Nunes de Moraes; Simone de Melo Costa; Antônio Prates Caldeira
ABSTRACT OBJECTIVE To estimate the prevalence of robustness among older adults assisted in primary health care and identify factors in successful aging. METHODS This is a cross-sectional study conducted with older adults in Northern Minas Gerais, Brazil. Two questionnaires were used for data collection: the Brazilian Older Americans Resources and Services Multidimensional Function Assessment Questionnaire (BOMFAQ) and the Clinical-Functional Vulnerability Index IVCF-20). The adjusted prevalence ratios were obtained by robust Poisson regression. Statistical analysis was performed for older adults in general (60 to 107 years) and stratified by age: from 60 to 79 years and 80 years or more. RESULTS A total of 1,750 older adults aged 60 to 107 years participated; between them, 48.7% were robust. Older adults aged 60 to 79 years (n = 1,421) and 80 years or more (n = 329) had a prevalence of robustness of 55.4% and 19.3%, respectively. Some factors associated with successful aging were: positive self-perception of health, dancing habits, walking habits, absence of cognitive impairment, absence of depressive symptoms and polypathology, as well as daily life independence. After adjustment by age, the absence of polypathology and independence for activities of daily living stand out for robustness between 60 and 79 years; in those aged 80 years and over, independence for activities of daily living and dance practice presented greater strength of association. CONCLUSION The prevalence of robust older adults in primary care is considered satisfactory for the older population in general but decreases with age and is associated with the absence of diseases and disabilities. These results denote the need to redesign the health care system, focusing on promoting and preventing clinical-functional vulnerability.